High-power blue laser pointer- induced maculopathy - Alsulaiman, Sulaiman (2013)
Purpose: To report various forms of maculopathy caused by momentary exposure to high-power blue laser pointer. Methods: A consecutive case series of patients who presented to the King Khaled Eye Specialist Hospital with a history of laser pointer exposure to the eye is reported. A full ophthalmic evaluation including fundus photography, spectral-domain optical coherence tomography and fluorescein angiography was performed. Results: Ten eyes of 10 patients were evaluated. The clinical findings included a full thickness macular hole in 3 eyes, subhyaloidal/sub internal limiting membrane ( ILM) hemorrhage in 4 eyes, an outer retinal disruption in one eye, an epiretinal membrane in 1 eye, and a schisis-like cavity in one eye. Nd:YAG hyaloidotomy was performed in three eyes with subhyloidal hemorrhage and pars plana vitrectomy (PPV) with or without tamponade in four eyes. Visual acuity improved in all patients spontaneously or following intervention. Four eyes (40%) improved spontaneously whereas 6 eyes (60%) were managed by Nd:YAG hyaloidotomy or surgery. Conclusions: Visual acuity improved in all patients spontaneously or following intervention. High-power handheld laser pointers are extremely dangerous to the eye and public awareness should be encouraged.